Adsorption Behaviors of Rubidium and Cesium Ions from Aqueous Solution onto Sodium Tetraphenylborate ‐ Polyacrylonitrile (TPB‐PAN). Issue 35 (19th December 2017) - Bao, Amin; Zheng, Hong; Liu, Zeyu; Huang, Dongfang
Abstract: In this study, a novel composite adsorbent of sodium tetraphenylborate – polyacrylonitrile (TPB–PAN) was prepared for investigating adsorption behaviors of rubidium (Rb) and cesium (Cs) ions from their aqueous solutions. Several experimental parameters such as pH, shaking time, initial concentration, and interference ions were routinely evaluated. The experimental results showed that the Rb(I) and Cs(I) were both adsorbed by the adsorbent of TPB‐PAN at pH 7.0, and the adsorption equilibriums were achieved within 2  h . The presence of co‐existing ions did not get involved with Rb(I) and Cs(I) adsorption, indicating the high selectivity of TPB‐PAN adsorbent toward Rb(I) and Cs(I) ions. Under optimum conditions, the maximum adsorption capacities for Rb(I) and Cs(I) ions by the adsorbent of TPB‐PAN were 44.64  mg g −1 and 118.48  mg g −1 based on the langmuir sorption isotherm study. In addition, the adsorption processes of rubidium and cesium both are exothermic spontaneous process. Therefore, the proposed adsorbent of TPB‐PAN allowed the selective, sensitive, easy to use, cost‐effective, high efficiency, fast kinetics of preconcentration and separation (removal) Rb(I) and Cs(I) ions even in the presence of competing ions. As a consequence, the TPB‐PAN adsorbent can be used potentially for preconcentration and separation Rb(I) and Cs(I) ions from water samples in a wide range of practical applications for removal Rb(I) and Cs(I) ions in environmental aqueous resources. Abstract : In this study, a novel composite adsorbent of sodium tetraphenylborate – polyacrylonitrile (TPB–PAN) was prepared for investigating adsorption behaviors of rubidium (Rb) and cesium (Cs) ions from their aqueous solutions. The adsorption equilibrium of Rb(I) and Cs(I) ions were achieved within 2  h at pH 7.0, and the maximum adsorption capacities were 44.64  mg g −1 and 118.48  mg g −1 according to langmuir adsorption isotherm. Therefore, the TPB‐PAN adsorbent can be utilized to adsorb Rb(I) and Cs(I) ions from water samples.